Soy protein and formulated meat products [ - Hoogenkamp, Henk W. (CABI, 2005)
An authoritative review of soya protein science and technology is presented, particularly in relation to meat formulations. Topics related to the major issues that face consumers and manufacturers, including healthy lifestyles, food safety and market dyamics, are also discussed. The book contains a large number of tables providing formulations for a range of products, including emulsified meats, sausage, pt??, poultry and other meat based foods.